2007
DOI: 10.1111/j.1365-2109.2006.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursery rearing of kalbasu, Labeo calbasu (Hamilton), at different stocking densities in outdoor concrete tanks

Abstract: The growth and survival of kalbasu, Labeo calbasu, was evaluated at stocking densities of 5, 10 and 15 million spawn ha À1 in nursery rearing in concrete tanks of 50 m 2 , each for a period of 25 days. Survival of fry was density dependent and signi¢cantly higher (54.5%) at 5 million ha À1 than those at10 million ha À1 (50.1%) and15 million ha À1 (46.9%). Similarly, growth and speci¢c growth rate were inversely related to the stocking density and varied signi¢cantly among the three densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
2
Order By: Relevance
“…Despite the variations in water quality parameters in both the sets of experiments, the parameters were within the tolerance limit of the major carp fry as also reported earlier (Jena, Aravindakshan & Singh ; Chakraborty, Miah, Mirza & Habib ; Sahu et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite the variations in water quality parameters in both the sets of experiments, the parameters were within the tolerance limit of the major carp fry as also reported earlier (Jena, Aravindakshan & Singh ; Chakraborty, Miah, Mirza & Habib ; Sahu et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; Sharma & Chakrabarti ; Rahman, Mazid, Rahman, Khan, Hossain & Hossain ; Sahu et al . ; Rahman, Zaher & Azimuddin ; Das, Jena, Mishra & Pati ; Rahman, Zaher, Azimuddin, Yeasmine, Khan & Arshad ). However, it was interesting to note that despite presence of greater number, the SGR, length and weight attainment of seed in T‐2 were similar to those in T‐1 ( P > 0.05) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seed rearing of these species has been often marred with poor growth and survival with the approximate spawn to fry and spawn to fingerling yield ratio generally at 3:1 and 6:1 respectively in earthen ponds. Most of the studies reported on the nursery rearing of carps (Jena et al, 1998a;Sahu et al, 2007;Das et al, 2016) have used simple mixture of powdered groundnut oil cake (GOC) and rice bran (RB) as feed supplements and the fry survival were limited to 30 to 60%. Probably, non-compliance of this supplementary feed mixtures to the nutritional requirement of carp from spawn to fry stage could be one of the major factors for such low survival as opined by many researchers (Varghese, 1976;Basavaraja and Antony, 1997;Das et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Em um experimento realizado com avaliação do desenvolvimento de peixes ornamentais (Labeo calbasu e Carassius auratus), concluiu-se que quando se aumenta a densidade de estocagem, diminui-se o desenvolvimento dos mesmos (SAHu et al, 2007;SoAReS et al, 2002). Segundo Stone e McnuLty (2003), esse resultado pode estar associado à diminuição da disponibilidade individual de alimento e à presença de metabólitos específicos da espécie.…”
Section: Resultsunclassified